CRAFTING MY OWN STORY: HOMELESS MOTHERS‟ STANDPOINTS USING THEMATIC NARRATIVE ANALYSES - Bertsch, Thérèse M. Craine (European Scientific Journal, ESJ, 2014)
Single mothers in the U S, especially women of color, face the greatest risk for homelessness in the current housing crisis. Eleven homeless single mothers produced their own findings on their experiences with recurrent episodes of homelessness. Feminist standpoint theory guided this qualitative study using a U. S. third world cultural lens. Thematic narrative analysis structured the women‘s steps to analyze and create their own narratives. Political and ideological splits suggested homelessness for young single mothers resulted from either their lack of motivation and poor choices, or the lack of affordable housing, poverty, and social capital. Researchers called for process research to identify the risks and protective factors for both individual and structural factors driving unstable housing. These findings suggest rental enhancement although necessary was not sufficient to obtain and maintain stable housing. Poor quality housing, rental hikes, sale of homes, abuse and people entering or leaving rentals were precursors of recurrent episodes of homelessness. Bourgeois social structures excluding poor women need to address the need for affordable housing and public services, and less restrictive shelter and surveillance regulations as barriers to stable housing and jobs. Given their experiences of poverty and trauma, it was a revelation that dedication to family (feeling ennobled by motherhood), and the desire to work — typical concerns of working mothers — were the predominant themes I uncovered as the social work researcher in my cross case analysis of the women‘s narratives. These findings challenge stigmatizing beliefs about neglectful mothering, and their lack of motivation for employment.